Pengembangan Media Pembelajaran dengan Pemanfaatan Aplikasi Wondershare Quizcreator - Isa, Yamanto; Sutiono, Edi; Rusdi, Mohamad Salman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to develop assessment media for learning using the Wondershare QuizCreator application in the Biology subject for Class XI Science at SMA Negeri 1 Cempaka OKU Timur. The research method used is the procedural engineering method employing survey-type data collection techniques. The research results show that media experts rated this product 85.3 in the